Patterned separator membranes with pillar surface microstructures for improved battery performance - Gonçalves, Renato Ferreira (2021)
In order to improve battery performance by tuning battery separator membranes, this work reports on porous poly(vinylidene fluoride-co-trifluoroethylene) - P(VDF-TrFE)- membranes with surface pillar microstructures. Separators with tailored pillar diameter, height and bulk thickness were fabricated by template patterning and computer simulations, allowing to evaluate the effect of the pillar microstructure characteristics on battery performance. It is shown that the different pillar microstructures of the separators affect the uptake value (150–325%), ionic conductivity value (0.8–1.6 mS·cm−1) and discharge capacity of the lithium ion batteries (LIB) when compared with the separator without pillars. The experimental charge-discharge behavior demonstrates that the pillar parameters affect battery performance and the best microstructure leading to 80 mAh·g−1 at 2C. Battery performance can be thus optimized by adjusting pillar diameter, height and bulk thickness of the separators keeping its volume constant, as demonstrated also by the simulation results. The parameter with most influence in battery performance is the bulk thickness of the separator, allowing to obtain a maximum discharge capacity value of 117.8 mAh·g−1 at 90C for a thickness of 0.01 mm. Thus, this work shows that the optimization of the pillar microstructure of the separator membranes allows increasing the capacity towards a new generation of high-performance LIBs.